Abrupt Geographical Transition between Aposematic Color Forms in the Spittlebug Prosapia ignipectus (Fitch) (Hemiptera: Cercopidae) - Vinton Thompson; Gervasio S. Carvalho (Psyche: A Journal of Entomology)
Over most of its range populations of the spittlebug Prosapia ignipectus (Fitch) (Hemiptera: Cercopidae) are monomorphic for black dorsal coloration. At the far northeastern margin of the species range in Maine, a cluster of populations is monomorphic for the presence of traverse orange dorsal lines against a black background. The narrow gap separating monomorphic black and monomorphic lined populations is less than 10 km wide, shows no evidence of a hybrid zone, and is without consequential physical barriers or ecological breaks. This sharp and unexpected division of color forms seems to have persisted for at least 90 years. It appears to be the sharpest divide ever recorded between geographically adjacent populations monomorphic for alternative aposematic color forms. About 45 kilometers to the southwest of this dividing line, three closely situated populations, surrounded by monomorphic black populations, are polymorphic for the two color forms. These observations are at variance with several expectations for aposematic species: (1) that local populations will be monomorphic for warning coloration, (2) that adjacent populations monomorphic for different local color forms will be linked by populations with mixed or hybrid forms, and (3) that geographic boundaries between contrasting aposematic color forms should be temporally unstable.